Bio-remediation of a sludge containing hydrocarbons - Ayotamuno, Josiah M.; Okparanma, Reuben N.; Nweneka, E. K.; Ogaji, Stephen O. T.; Probert, Sydney D. (Elsevier, 2007)
Bio-augmentation has been used as a bio-remediation option for hydrocarbon-contaminated, oily-sludge restoration. This sludge was obtained from the Bonny-Terminal Improvement Project (BTIP) for Bonny Island, near Port Harcourt, Nigeria. Its total hydrocarbon-content (THC) was 69,372 mg/kg of sludge. Three treatment reactors (X, Y and Z) and one control reactor (A) were charged with 1500 g of oily sludge and 250 g of agricultural soil (i.e. an oily sludge to soil ratio of 6:1), the mixture homogenized and allowed to settle for seven days before various CFUs were added to reactors X, Y and Z. Reactor A did not receive any bio-preparation. The agricultural soil served both as a nutrient and a microbe carrier. With regularly scheduled mixing and watering, the THC reduction in the oily sludge varied between 40.7% and 53.2% within two weeks as well as between 63.7% and 84.5% within six weeks of applying the bio-remediation. The CFU counts of the added bio-preparation varied between 1.2 × 1212 and 3.0 × 1012 CFU/g of sludge and decreased to 7.0 × 1011 CFU/g of sludge by the end of the sixth week. The pH of the degrading sludge fluctuated between 6.5 and 7.8 during the same period. When compared with the performance of the indigenous microbes in the control sample, the added bio-preparation evidently increased the THC reduction rate in the oily sludge.
Keywords: Bio-remediation; Oily sludge; Bio-augmentation; Terminal operations